Diagnostic layering: Patient accounts of breast cancer classification in the molecular era. (June 2021) - Ross, Emily; Swallow, Julia; Kerr, Anne; Chekar, Choon Key; Cunningham-Burley, Sarah
Abstract: Social scientific work has considered the promise of genomic medicine to transform healthcare by personalising treatment. However, little qualitative research attends to already well-established molecular techniques in routine care. In this article we consider women's experiences of routine breast cancer diagnosis in the UK NHS. We attend to patient accounts of the techniques used to subtype breast cancer and guide individual treatment. We introduce the concept of 'diagnostic layering' to make sense of how the range of clinical techniques used to classify breast cancer shape patient experiences of diagnosis. The process of diagnostic layering, whereby various levels of diagnostic information are received by patients over time, can render diagnosis as incomplete and subject to change. In the example of early breast cancer, progressive layers of diagnostic information are closely tied to chemotherapy recommendations. In recent years a genomic test, gene expression profiling, has become introduced into routine care. Because gene expression profiling could indicate a treatment recommendation where standard tools had failed, the technique could represent a 'final layer' of diagnosis for some patients. However, the test could also invalidate previous understandings of the cancer, require additional interpretation and further prolong the diagnostic process. This research contributes to the sociology of diagnosis by outlining how practices of cancer subtyping shape patient experiences of breast cancer. We add to social scientific work attending to the complexities of molecular and genomic techniques by considering the blurring of diagnostic and therapeutic activities from a patient perspective. Highlights: Molecular techniques are embedded within contemporary UK breast cancer care. Routine diagnostic practices 'split' breast cancer into subtypes. The diversity of diagnostic techniques can render diagnosis both partial and subject to change. We capture these experiences from a patient perspective with the concept of 'diagnostic layering'. Gene expression profiling could finalise, but also prolong, diagnostic processes.